Situations and demands of central sterile supply department training on nursing interruptions - Juanli Huang; Liangying Yi; Kaili Wu; Yanhua Chen; Ruixue Hu; Wei Pan; Ting Hu; Sixin Jiang (BMC Health Services Research)
Abstract Backgrounds Central sterile supply department (CSSD) is an important department in the hospital. It can ensure successful sterilization and nosocomial infection control. CSSD staff are often interrupted during cleaning, disinfection, packaging, sterilization and distribution. This study investigated nursing interruptions in CSSDs in China, aiming to understand the current situations and demands of CSSD training on nursing interruptions. It also examined whether there were differences in training on nursing interruptions among CSSD nurses with different characteristics, so as to provide a reference for developing CSSD training for nursing interruptions. Methods A self-designed questionnaire was used to investigate the current situations and demands of CSSD training on nursing interruptions. A total of 2528 CSSD nurses from different levels of hospitals in different regions of China were recruited using convenience sampling during June to August 2023. Results A total of 648 (25.63%) CSSD nurses had received training on nursing interruptions. A total of 2149 nurses (85.01%) believed that it was necessary to conduct systematic training on nursing interruptions. Statistically significant differences (P < 0.05) in rates of CSSD nurses who received training on nursing interruptions were identified among the nurses with different genders, age, education attainments, length of service and job positions. The rate of male nurses who received training on nursing interruptions was higher than female nurses. The rate of younger nurses who received the training was higher than older nurses. Nurses who possessed a master’s degree or a doctorate degree had a higher rate of receiving training on nursing interruptions than the nurses who possessed an associate degree or a bachelor’s degree. Nurses with 1–5 years of service had a higher rate of receiving the training than nurses with a longer length of service. Conclusions CSSD nurses have a high demand for training on nursing interruptions, but the current training is insufficient. Nursing managers should pay attention to the training of nurses with different characteristics. Training on nursing interruptions should focus on improving CSSD nurses’ professional skills, risk awareness of nursing interruptions and self-concentration ability, so as to improve CSSD nurses’ cognition and coping ability of nursing interruptions.